1968 and rural Japan as a site of struggle. Approaches to rural landscapes in the history of Japanese documentary film. Issue 2 (3rd July 2021) - Centeno-Martín, Marcos P.
ABSTRACT: In the twentieth century, Japan produced an extraordinary documentary film heritage around the rural world which has not received sufficient attention. This article identifies three different approaches to the rural in Japanese film history: first, the wartime interest in place as providing an "authentic essence" of a national identity. Second, the postwar representation of the rural in public relations films ( PR eiga ), mainly interested in geography. And third, the release of Ogawa's Summer in Sanrizuka in 1968 which brought a new dimension to a countryside transformed into both a battlefield and an icon of the political protest of the era.